The Role and Meaning of Religion for Korean Society - Lee, Song-Chong (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This special issue presents discussions of the role and meaning of religion for Korean society. Covering wide-ranging time periods, the authors explores with their own cases four major characteristics of Korean religion: Creativity, Greater Responsiveness, Adaptability, and Prophethood. Their topical religious traditions include Neo-Confucianism, Christianity, Buddhism, and Korean new religious movements.